Effect of Electromagnetic Field on Crop Branches During Flowering Periods of Cotton Under Norinal and Water Deficit Conditions - IBRAGIMOVA Z. Yu; YULDASHEVA Sh.B (Zien Journals, 2023)
The article presents an analysis of the researches obtained as a result of the study of the influence of electromagnetic waves on the growth and development of cultivars and the variability of some economic characteristics in the conditions of water shortage. Based on the obtained results, it was determined that cultivar plants have different responses to unfavorable conditions and low-frequency electromagnetic waves before planting, indicating that they belong to heterogeneous and homogeneous populations or depend on their genotypic status.
Keywords: genotype; genetic collection; cotton; variety; line; electromagnetic induction, stress